2019
DOI: 10.1158/1078-0432.ccr-19-0081
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of CD8+ T Cells via CXCR4 Blockade Facilitates PD-1 Checkpoint Therapy in Human Pancreatic Cancer

Abstract: Purpose: Pancreatic ductal adenocarcinoma (PDA) is rarely cured, and single-agent immune checkpoint inhibition has not demonstrated clinical benefit despite the presence of large numbers of CD8+ T cells. We hypothesized that tumor-infiltrating CD8+ T cells harbor latent anti-tumor activity that can be reactivated using combination immunotherapy. Experimental Design: Preserved human PDA specimens were analyzed using multiplex immunohistochemistry (IHC) and T cell receptor (TCR) sequencing. Fresh tumor was tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
182
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 47 publications
3
182
0
Order By: Relevance
“…Already used for TKI targeted therapies, these models are increasingly being considered as potential platforms for monitoring immunotherapy responses [89]. Recent studies indeed reported an active immune TME after applying immunomodulatory molecules on tumour slice organotypic cultures, opening the way for their study on 3D ex vivo tumour models [90]. Interestingly, co-cultures of tumour-derived organoids were enriched with lymphocytes, leading Dijkstra and collaborators to recently demonstrate the generation of tumour-reactive T cells by co-culture of peripheral blood lymphocytes and colorectal cancer-derived organoids [91].…”
Section: D Culture Modelsmentioning
confidence: 99%
“…Already used for TKI targeted therapies, these models are increasingly being considered as potential platforms for monitoring immunotherapy responses [89]. Recent studies indeed reported an active immune TME after applying immunomodulatory molecules on tumour slice organotypic cultures, opening the way for their study on 3D ex vivo tumour models [90]. Interestingly, co-cultures of tumour-derived organoids were enriched with lymphocytes, leading Dijkstra and collaborators to recently demonstrate the generation of tumour-reactive T cells by co-culture of peripheral blood lymphocytes and colorectal cancer-derived organoids [91].…”
Section: D Culture Modelsmentioning
confidence: 99%
“…An additional caveat of the xenograft slice cultures is that a human tumor grows in a non-native mouse microenvironment. Studies with tissue that retains the native microenvironment may also facilitate the testing of newer agents, such as shown in slice culture for immune check-point inhibitors 14,42 and adenovirus-based therapies 43 , alone or in combination with conventional targeted or genotoxic drugs. For example, Seo et al recently demonstrated a response to immunotherapy with combined PD-1 and CXCR4 blockade in human pancreatic cancer slices 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with tissue that retains the native microenvironment may also facilitate the testing of newer agents, such as shown in slice culture for immune check-point inhibitors 14,42 and adenovirus-based therapies 43 , alone or in combination with conventional targeted or genotoxic drugs. For example, Seo et al recently demonstrated a response to immunotherapy with combined PD-1 and CXCR4 blockade in human pancreatic cancer slices 42 . The use of patient tumor tissue will permit studies with a native human microenvironment, and complementary studies in the future with syngeneic or transgenic mouse tumor models could exploit the intact mouse microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Agonist anti-CD40 therapy with chemotherapy reversed the complete resistance of murine pancreatic tumors to PD-1 and CTLA-4 blockade [ 36 ]. Endogenous tumor-reactive T cells are present within the human PDAC tumor microenvironment and can be reactivated by combined blockade of PD-1 and C-X-C chemokine receptor 4 (CXCR4) [ 37 ]. These preclinical observations argue against the currently accepted paradigm that PDAC does not respond to immunotherapy due to a lack of immunogenicity or generation of tumor-reactive T cells.…”
Section: Discussionmentioning
confidence: 99%